Pembentukan Karakter Peserta Didik SDIT Insan Madani di era Pembelajaran Daring - Bulu', Rifa'ah Mahmudah; Sartika, Sartika; Bulu', Bulu' (Jurnal Ilmu Pendidikan Dasar Indonesia, 2022)
The pandemic period due to COVID-19 has caused changes in learning methods from offline to online to be a challenge for education providers. The impact of technological developments so that uncontrolled access has an impact on children's development, especially in character building. During this online learning period, many students' behavior became less disciplined, independent and even abandoned the Islamic etiquette that was applied in schools before the pandemic. The purpose of this study was to look at the role of teachers and parents in online learning on character education for students at SDIT Insan Madani Palopo. The research method used is qualitative research with a descriptive approach. The results showed that teachers at SDIT Insan Madani in forming honest, disciplined, religious and independent characters carried out their roles as correctors, informants, mediators, initiators and the teaching role was helped by the role of parents at home as facilitators, motivators, mentors and directors. However, there are obstacles faced in character building during online learning, namely network problems, students have not adapted well to changes in learning methods, time management from parents and different educational backgrounds from parents. Keywords: Teacher; Parent; online; character building